1992
DOI: 10.1104/pp.99.2.707
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid-Induced Chilling Tolerance in Maize Suspension-Cultured Cells

Abstract: The induction of chilling tolerance by abscisic acid (ABA) in maize (Zea mays L. cv Black Mexican Sweet) suspension cultured cells was examined. Cell viability during exposure to chilling was estimated by triphenyl tetrazolium chloride reduction immediately after chilling and a filter paper growth assay. Both methods yielded comparable results. Chilling tolerance was induced by transferring 5-day-old cultures (late log phase) to a fresh medium containing ABA (10 to 100 micromolar). The greatest chilling tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 23 publications
1
42
1
2
Order By: Relevance
“…The CH, at 1 PM, inhibits the ABA-induced chilling tolerance by 60% in maize suspension-cultured cells with a similar degree of inhibition in protein synthesis ( Fig. 5A; Xin and Li, 1992). In contrast, Pro-induced chilling tolerance was not inhibited by CH at 1 p~ (Fig.…”
Section: Effect Of Ch On Chilling Tolerance and Protein Synthesis In mentioning
confidence: 89%
See 4 more Smart Citations
“…The CH, at 1 PM, inhibits the ABA-induced chilling tolerance by 60% in maize suspension-cultured cells with a similar degree of inhibition in protein synthesis ( Fig. 5A; Xin and Li, 1992). In contrast, Pro-induced chilling tolerance was not inhibited by CH at 1 p~ (Fig.…”
Section: Effect Of Ch On Chilling Tolerance and Protein Synthesis In mentioning
confidence: 89%
“…3). We have reported that ABA-induced chilling tolerance can be inhibited by CH (Xin and Li, 1992). To determine further the relationship of Pro-induced chilling tolerance to ABA, we examined the effect of CH on the Proinduced chilling tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations